Early Warning System for Sana'a Water Stream (Al-Saila) - El-Kustaban, Amin; Qahtan, Abdullah; Al-Yousfi, Eyas; Al-Twaiti, Maged; Al-Mhjari, Maroof (University of Science and Technology, Yemen, 2014)
The early warning systems for flood disaster develop with the technologies fast growth. These warning systems early alert people against flood disaster. Many proposed systems use high techniques to alert for flood such as, Short Message Service (SMS) via Global System for Mobile communications (GSM); however, they are still complex to program and interface, in addition to their high cost. This paper proposes a simple and low cost early warning system using Arduino board, which is used to control the whole system and GSM shields to send and receive data. This work applies on specific region in Yemen, which is Al-Saila. The proposed system determines the water levels using float sensors. Then it analyzes the collected data and makes the proper decision. The GSM network is used to connect the overall system units via SMS. The system has been designed and implemented based on two components, Hardware and Software. The system units are powered from the main supply in addition to solar cell